The Influence Of Role Conflict, Social Support, And Work Life Balance On Psychological Well-being And Women's Career Development At Hope Christian Education Foundation - Dewi, Ni Made Rai Kristiana; Komalasari, Yeyen; Joko Adinegara, I Gusti Ngurah; Purnama Trimurti, Christimulia (The Es Economics and Entrepreneurship, 2024)
This research aims to explore the influence of role conflict, social support, and work-life balance on the psychology well-being and career development of women at Christian College Foundation Hope. The study employs a quantitative approaches using questionnaires, interviews, observations, and literature review methods. Data analysis will be conducted using Partials Least Squares (PLS), which is a component of the Structural Equations Modeling (SEM) framework. The results indicate that family social support has a negative influence on dual-role conflict. Higher family social support is associated with lower levels of dual-role conflict experienced by women, thus minimizing such conflicts and aiding women in focusing more on their career development. Additionally, achieving a balance between life and work is a crucial need for individuals in seeking meaning and quality in their lives. Therefore, social support from both family and work environments is essential for women to pursue their careers without neglecting other roles. The findings of this research are expected to contribute to a better understanding of the dual-role conflicts experienced by working women and their impacts on career development.